Vulnerability and young people care and social control in policy and practice - Brown, Kate 1980- (Policy Press, 2015)
This book draws on in-depth research with marginalised young people and the professionals who support them to explore the implications of a 'vulnerability zeitgeist', asking how far the rise of vulnerability in welfare and criminal justice processes serves the interests of those who are most disadvantaged